Impact of Foreign Direct Investment on Gross Domestic Product in Nepal - Baral, Shiva Datta; Thapa, Bandana (Journal of Development and Social Engineering, 2025)
Foreign direct investment is a critical component in the development of modern-era economies, and especially in developing nations. FDI can help create jobs, increase productivity, increase exports, and technology transfer, thus contributing to sustained economic growth. This research intends to assess the impact of FDI on GDP of Nepal using the ARDL model utilizing the annual time series data ranging from 1993/1994 through 2023/2024. In this research, unit root tests were performed to find the integration order of the variables. Cointegration between the variables were performed through the ARDL Bound Test. Later on, in accordance with the test, long-run coefficients and Error Correction Model (ECM) were estimated in order to interpret the findings in the context of equilibrium and adjustment in the system. Findings of this research have revealed that FDI’s impact on GDP in the short run is positive but less significant and in the long run, FDI’s impact on GDP is positive and significant.